Pengaruh pH dan Konsentrasi Terhadap Penyerapan Ion Logam Pb2+ Menggunakan Kulit Buah Matoa (Pometia pinnata) - Deva Indriyani; Edi Nasra; Budhi Oktavia; Hesty Parbuntari; Desy Kurniawati (Periodic, 2023)
This research study was to determine the optimum conditions for the absorption of Pb2+ metal ions using the matoa fruit peel (Pometia pinnata) using the batch method with variations in pH, concentration, particle size, contact time and stirring speed. The results of the study showed that the optimum conditions for the absorption of Pb2+ occurred at pH 5, a concentration of 300 ppm with an absorption capacity of 34.015 mg/g. Pb2+ metal adsorption isotherm with matoa skin biosorbent (Pometia pinnata) tends to follow the Freundlich isotherm equation with a determinant coefficient (R) of 1.Keywords : Biosorption, Pb2+ metal, Pometia pinnata, Batch method